DESIGNING â€œE-PONâ€ TO TEACH NARRATIVE TEXT IN SENIOR HIGH SCHOOL - Maulana, Aziz; Ikhsanudin, Ikhsanudin; Wardah, Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was conducted to design E-PON; an electronic presentation as a teaching and learning media of narrative text. The purpose of this research is to find out whether or not E-PON as the supplementary teaching media is useable to teach narrative text in twelfth grade students of senior high school. The form of this research is developmental research. This developmental research was conducted to produce innovate teaching material. The method of this research consists of four phases namely analyzing, designing, developing, and implementing or called ADDI. The designed product was completed by combining West Kalimantanâ€™s local story with the electronic presentation to teach narrative text. The E-PON was designed for about 45 minutes. The completed research was implemented in the first semester of twelfth grade students in SMA Negeri 1 Sambas. There were 35 students who actively involved in this research. To sum up, it is found that E-PON is usable for teaching narrative text in twelfth grade students of senior high school.Keywords: Development Research, E-PON, Narrative Text